Workspace analysis of an R (2-UPR/2-UPS) hybrid machine tool - Yin, Zuwang; Wang, Dong; Zhou, Xiaoguang; Wu, Jiahua (Journal of physics. Conference series, 2025)
This paper proposes a hybrid machine tool with an R (2-UPR/2-UPS) asymmetric layout. Its workspace is analyzed, that is, the set of accessible positions of the spindle tool head point under the condition that the motion range of each hinge is met. The workspace of the mechanism is an important component for analyzing the movement of the mechanism and an important indicator for evaluating the processing performance of the machine tool. An intuitive understanding of the workspace and analysis of the tool’s posture and position performance in the workspace are conducive to fully utilizing the processing capacity of the machine tool and improving the processing efficiency of the machine tool.